2006
DOI: 10.1128/jcm.44.3.1159-1164.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Species Combined into the Burkholderia cepacia Complex and Related Taxa on the Basis of Their Fatty Acid Patterns

Abstract: Using the established commercial system Sherlock (MIDI, Inc.), cellular fatty acid methyl ester analysis for differentiation among Burkholderia cepacia complex species was proven. The identification key based on the diagnostic fatty acids is able to discern phenotypically related Ralstonia pickettii and Pandoraea spp. and further distinguish Burkholderia pyrrocinia, Burkholderia ambifaria, and Burkholderia vietnamiensis.At present, nine Burkholderia species are combined into the Burkholderia cepacia complex (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The wholecell fatty acid compositions of the group C isolates (Table 1) show that 2-hydroxy-tetradecanoic acid was practically absent but 3-hydroxy-tetradecanoic acid and 3-hydroxy-hexadecanoic acid were abundant (4-5%). This matches with the identiWcation of the isolates as members of the betaproteobacterial B. cepacia complex species other than B. pyrrocinia, B. ambifaria, or B. vietnamiensis [25].…”
Section: Resultssupporting
confidence: 67%
“…The wholecell fatty acid compositions of the group C isolates (Table 1) show that 2-hydroxy-tetradecanoic acid was practically absent but 3-hydroxy-tetradecanoic acid and 3-hydroxy-hexadecanoic acid were abundant (4-5%). This matches with the identiWcation of the isolates as members of the betaproteobacterial B. cepacia complex species other than B. pyrrocinia, B. ambifaria, or B. vietnamiensis [25].…”
Section: Resultssupporting
confidence: 67%
“…First, the organism must be cultured under standardized growth conditions. This requirement stems from the fact that fatty acid composition is influenced by growth medium and incubation temperature (Krejci and Kroppenstedt ). Second, sample preparation for this method includes several time‐consuming and complicated steps (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, it did not give clear evidence about the classification of strain GB-01. The high % of 18 0 fatty acid (5.1%) indicated that GB-01 should be closely related to B. vietnamiensis, because 3% value for this fatty acid is a typical characteristic of B. vietnamiensis species (Krejci and Kroppenstedt, 2006). However, phylogenetic analysis of 16S rRNA and recA genes (discussed below) of strain GB-01 illustrated its close relationship with B. ambifaria and B.diffusa rather than B. vietnamiensis.…”
Section: Whole Cell Fatty Acid Profile Of Strain Gb-01mentioning
confidence: 99%
“…The comparison of fatty acid profiles of strain GB-01 with some type strains of genus Burkholderia and other closely related genera, expressed as relative abundance (%), is shown in Table 3. Krejci and Kroppenstedt (2006) and Sheu et al (2013). ** It was detected as Summed feature 3, that may comprise C 15:0 iso 2OH, and/or C 16:1 ω7c, and/or C 16:1 ω6c or any combination of these.…”
Section: Whole Cell Fatty Acid Profile Of Strain Gb-01mentioning
confidence: 99%